Flexible optical cable skin with high bending resistance and preparation method thereof

Through the combination of modified polyvinyl chloride and PBT resin, combined with modified fillers and other additives, the performance problems of the skin of submarine communication optical cables in extreme environments are solved, and the bending, stretching and oil resistance are improved, meeting the high-performance needs of submarine optical cables.

CN119505442AInactive Publication Date: 2025-02-25JIANGSU SMART WORKSHOP TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411721143.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The skin of existing submarine communication optical cables is prone to problems such as hygroscopicity, moisture resistance, corrosion resistance, mechanical strength and temperature resistance in extreme environments, especially when the coating is easily peeled off under bending conditions, which cannot meet market demand.

Method used

The combination of modified polyvinyl chloride, PBT resin, modified filler, plasticizer, lubricant, anti-hydrolyzer and molding agent is adopted to improve the tensile performance and oil resistance of the optical cable skin through the use of modified nitrile rubber and vinyl silicone oil, and improve the repeated bending durability of the optical cable by combining PBT resin.

Benefits of technology

It significantly improves the bending, tensile and oil resistance of the optical cable skin, ensuring the stability and long-term reliability of the optical cable in complex subsea environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005158064010000131
    Figure BDA0005158064010000131
Patent Text Reader

Abstract

The invention provides a flexible optical cable skin with high bending resistance and a preparation method thereof. The flexible optical cable skin with high bending resistance comprises the following components in parts by weight: 100 parts of modified polyvinyl chloride, 15-20 parts of PBT resin, 18-23 parts of a modified filler, 60-65 parts of a plasticizer, 0.4-0.9 part of a lubricant, 1-2 parts of an anti-hydrolysis agent and 1-3 parts of a forming agent. The flexible optical cable skin with high bending resistance is excellent in bending resistance, good in tensile property and high in oil resistance, and can be used for preparing submarine optical cables.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of optical cables, and in particular relates to a flexible optical cable skin with strong bending resistance and a preparation method thereof. Background Art

[0002] The outer sheath of the optical cable is an important component that protects the internal optical fiber from damage by the external environment. Underwater communication optical cables (submarine optical cables) are important communication infrastructure connecting different continents or islands, used to transmit large amounts of data, voice and video information. Compared with terrestrial optical cables, underwater optical cables face more stringent environmental conditions and higher technical requirements.

[0003] In the field of submarine communications, optical cables may experience extremely complex environmental conditions. In this case, optical cables must have excellent performance to ensure their normal operation. Polyvinyl chloride (PVC), as a common optical cable material, has shown good performance in many applications, but there are some technical problems in its use in the field of submarine communication optical cables: 1. Water resistance and moisture resistance. The humidity of the submarine environment is extremely high. The hygroscopicity of PVC materials is strong and it is easy to absorb moisture, resulting in a decrease in material performance. Water penetration into the interior of the optical cable may cause an increase in optical fiber loss and affect the quality of signal transmission. 2. Corrosion resistance. The submarine environment contains salt and other corrosive substances. PVC materials may degrade after long-term exposure to these substances. Material degradation will cause the mechanical strength and electrical properties of the optical cable to decrease, shortening the service life of the optical cable. 3. Mechanical strength. The mechanical strength and toughness of PVC materials are relatively poor, especially in low temperature and high pressure environments, and embrittlement is prone to occur. 4. Temperature resistance. The temperature of the submarine environment varies greatly. PVC materials may soften at high temperatures and become brittle at low temperatures. Temperature changes may cause the physical properties of the optical cable to be unstable, affecting its long-term reliability.

[0004] The existing technology can improve the application of PVC materials in submarine optical cables to a certain extent through the following methods: (1) Modified PVC: By adding modifiers, such as plasticizers, stabilizers, antioxidants, etc., the water resistance, corrosion resistance and mechanical strength of PVC materials can be improved. (2) Composite materials: PVC is compounded with other high-performance materials (such as polyethylene, polyurethane, etc.) to improve the overall performance. (3) Multi-layer structure: Design a multi-layer structure of the outer sheath of the optical cable, the outer layer uses corrosion-resistant and wear-resistant materials, and the inner layer uses PVC materials to balance cost and performance. (4) Coating technology: Coat a layer of corrosion-resistant and UV-resistant coating on the surface of the outer sheath to improve the protective performance of the optical cable. The coating technology commonly used at present has insufficient adhesion between the coating and the outer sheath, which may cause the coating to fall off or peel off. In particular, the optical cable in submarine communications may experience extreme bending radius, which is more likely to cause the coating to fall off and cannot meet the needs of the existing market.

[0005] Therefore, there is an urgent need for a flexible optical cable skin with strong bending resistance and a preparation method thereof. Summary of the invention

[0006] The purpose of the present invention is to provide a flexible optical cable skin with strong bending resistance and a preparation method thereof.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A flexible optical cable skin with strong bending resistance comprises the following components in parts by weight: 100 parts of modified polyvinyl chloride, 15-20 parts of PBT resin, 18-23 parts of modified filler, 60-65 parts of plasticizer, 0.4-0.9 parts of lubricant, 1-2 parts of anti-hydrolysis agent and 1-3 parts of molding agent;

[0009] The preparation method of modified polyvinyl chloride comprises the following steps:

[0010] (1) mixing nitrile rubber, vinyl silicone oil, dicumyl peroxide and toluene in a weight ratio of 100:(20-25):(1-2):(870-900), stirring at 25-30° C. for 1-2 hours to obtain a mixed solution, reacting the mixed solution at 100-110° C. for 4-5 hours under nitrogen protection, cooling, ethanol precipitation, and drying to obtain a modified nitrile rubber;

[0011] (2) Mixing polyvinyl chloride and modified nitrile rubber in a weight ratio of 100:(10-15) to obtain a mixed raw material; putting the mixed raw material into a twin-screw extruder to react for 15-20 minutes, extruding, pelletizing, and drying to obtain modified polyvinyl chloride.

[0012] Further, the temperatures of each zone of the twin-screw extruder are as follows: zone 1 180-190°C, zone 2 200-210°C, zone 3 210-220°C, zone 4 210-220°C, zone 5 200-210°C, zone 6 200-210°C, zone 7 200-210°C, zone 8 210-220°C, zone 9 210-220°C, and die head 200-210°C.

[0013] Furthermore, the molecular weight of the vinyl silicone oil is 9400, the vinyl content is 0.4-0.6 wt %, and it is purchased from Anhui Mingyi Silicon Industry Co., Ltd., model MY273 vinyl silicone oil.

[0014] With the continuous development of submarine optical cable technology, the polyvinyl chloride currently on the market cannot meet the requirements of submarine optical cable for tensile properties. The present invention can improve the tensile properties of the optical cable skin by modifying polyvinyl chloride. The modified butyl rubber prepared by vinyl silicone oil can improve the fluidity during the mixing process, ensure the uniform dispersion of each component, promote the cross-linking reaction between polyvinyl chloride and nitrile rubber, and the cross-linking structure can enhance the cohesion of the material. Through the modification treatment, the compatibility of polyvinyl chloride and nitrile rubber is improved, so that the interface of the two is more closely bonded, and the mechanical properties are improved.

[0015] Further, the polyvinyl chloride resin includes polyvinyl chloride resin I, polyvinyl chloride resin II and polyvinyl chloride resin III in a weight ratio of (1.4-1.7):1:(0.3-0.5); the average degree of polymerization of polyvinyl chloride resin I is 1300±50, the K value is 71-72, Formosa Plastics Industry (Ningbo) Co., Ltd., model S-70R; the average degree of polymerization of polyvinyl chloride resin II is 2500±200, the K value is 84-85, Formosa Plastics Industry (Ningbo) Co., Ltd., model S-85; the average degree of polymerization of polyvinyl chloride resin III is 1800±50, the K value is 77-78, Formosa Plastics Industry (Ningbo) Co., Ltd., model S-80.

[0016] Among them, the K value of polyvinyl chloride is a parameter that characterizes its molecular weight, and is mainly used to describe the average degree of polymerization of PVC resin. The K value is closely related to the viscosity and molecular weight of PVC, and can be calculated by measuring the solution viscosity of PVC in a specific solvent. The larger the K value, the higher the molecular weight of PVC, and the higher the corresponding degree of polymerization.

[0017] Further, the PBT resin includes PBT resin I, PBT resin II and PBT resin III in a weight ratio of (0.2-0.5): (1.4-1.6): 1, PBT resin I has a melt flow rate of 80g / 10min at 250°C / 2.16kg, a tensile modulus of 2700MPa, and a flexural modulus of 2500MPa at a span of 50.0mm, model: HX215HP SabicValoxPBT; PBT resin II ... The melt flow rate is 26g / 10min, the tensile modulus is 9300MPa, and the flexural modulus at a span of 50.0mm is 7580MPa. Model: HX420HP SabicValoxPBT; the melt flow rate of PBT resin III at 250℃ / 2.16kg is 12g / 10min, the tensile modulus is 8840MPa, and the flexural modulus at a span of 50.0mm is 7400MPa. Model: K4560 SabicValoxPBT.

[0018] The present invention attempts to add PBT resin to improve the durability of the optical cable under repeated bending conditions, but the effect is not ideal. The present invention can improve the durability of the optical cable under repeated bending conditions by compounding three different PEB resins and adding them to the system of the present invention. Analysis shows that the three different types of PBT resins have different performance characteristics, and the performance can be complemented and optimized through compounding. In the compounding process, they can interact with each other, improve compatibility, reduce phase separation, and reduce stress concentration points. By compounding three PBT resins with different characteristics and adding them to the polyvinyl chloride system, the performance can be complemented and optimized, and the toughness, rigidity and processing performance of the material can be improved, thereby significantly improving the durability of the optical cable under repeated bending conditions.

[0019] Furthermore, the preparation method of the modified filler comprises the following steps:

[0020] (1) mixing single-walled carbon nanotubes, nano-alumina and nano-silicon dioxide in a weight ratio of 1: (1.2-1.4): (0.5-0.7) to obtain a mixed filler;

[0021] (2) Mixing a mixed filler, anhydrous ethanol and KH550 in a weight ratio of 1: (10-12): (0.2-0.4), stirring and reacting at 55-60° C. for 4-6 hours, filtering, washing and drying to obtain a pre-modified filler;

[0022] (3) Pre-modified filler, anhydrous ethanol, glycidyl methacrylate and azobisisobutyronitrile in weight parts of 1: (8-10): (0.15-0.18): (0.02-0.04) are mixed, heated at 60-65° C. with stirring for 6-8 hours, filtered, washed and dried to obtain a modified filler.

[0023] Furthermore, the single-walled carbon nanotube has a diameter of 1-2 nm, a length of 5-30 μm, and a specific surface area of ​​120 m 2 / g; the particle size of nano-alumina is 15-20nm, and the specific surface area is 150-200m 2 / g; the particle size of nano-silicon dioxide is 10-15nm, and the specific surface area is 250m 2 / g.

[0024] In the submarine environment, the optical cable may come into contact with various oil substances, such as petroleum, lubricating oil and other organic compounds. These oil substances may have adverse effects on the materials of the optical cable, thereby affecting the performance and life of the optical cable. The present invention attempts to add fillers to the system to improve the oil resistance, but the effect is not ideal. By modifying the filler, the oil resistance of the optical cable can be improved. Analysis shows that the interface bonding between the filler and the PVC matrix is ​​weak, resulting in the filler being unable to effectively transfer stress. Through the modification treatment, an epoxy group with good compatibility with the PVC matrix is ​​introduced onto the surface of the filler. The filler forms a denser physical barrier in the PVC matrix, effectively blocking the penetration of oil substances and improving the oil resistance of the material.

[0025] When fillers with specific parameters, polyvinyl chloride resins with specific parameters, and PBT resins with specific parameters are used, the bending resistance of optical cables at low temperatures can be improved. This is mainly because the interface between the modified fillers and the polyvinyl chloride resin and PBT resin matrix is ​​more tightly bonded under this condition, which can effectively transfer stress, work synergistically at multiple scales, improve the flexibility and crack resistance of the material, and prevent stress concentration and crack propagation at low temperatures.

[0026] Furthermore, the plasticizer is adipic acid polyester or trioctyl trimellitate.

[0027] Furthermore, the molding agent is an acrylate copolymer.

[0028] Furthermore, the anti-hydrolysis agent is polycarbodiimide.

[0029] Furthermore, the lubricant is at least one of natural paraffin, liquid paraffin, microcrystalline paraffin, and polyethylene wax.

[0030] The invention provides a method for preparing the flexible optical cable sheath with strong anti-bending performance, comprising the following steps: adding modified polyvinyl chloride, modified filler, plasticizer, lubricant and anti-hydrolysis agent to a high-speed mixer in sequence, controlling the temperature at 155-160° C. and mixing for 15-20 minutes; cooling to 100-105° C., adding a molding agent, mixing for 5-10 minutes, heating to 145-150° C., adding PBT resin, mixing for 10-15 minutes, discharging the material, adding the material to a twin-screw extruder granulator, extruding and granulating at 135-140° C. to obtain an optical cable material, and preparing the optical cable material into an optical cable sheath, namely, a flexible optical cable sheath with strong anti-bending performance.

[0031] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0032] 1. The present invention can improve the tensile properties of the optical cable skin by modifying polyvinyl chloride.

[0033] 2. The present invention can improve the durability of the optical cable under repeated bending conditions by compounding three different PEB resins and adding them to the system of the present invention.

[0034] 3. The present invention can improve the oil resistance of the optical cable surface by modifying the filler.

[0035] 4. When fillers with specific parameters, polyvinyl chloride resins with specific parameters, and PBT resins with specific parameters are used, the bending resistance of optical cables at low temperatures can be improved. DETAILED DESCRIPTION

[0036] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] The raw materials used in the following examples of the present invention are all commercially available products:

[0038] Nitrile rubber, Shandong Qiyun Chemical Technology Co., Ltd., liquid nitrile rubber, acrylonitrile content wt30%.

[0039] Acrylate copolymer, DuPont, USA, brand EMA 1214AC.

[0040] Polycarbodiimide, Shanghai Youen Chemical Co., Ltd., model UN-150.

[0041] Liquid paraffin, Merck KGaA, Darmstadt, Germany, catalog number 76233.

[0042] Trioctyl trimellitate, Shandong Yueyang New Materials Co., Ltd., CAS No. 319-31-1.

[0043] Natural paraffin wax, Tianjin Vancos Technology Co., Ltd.

[0044] Example 1

[0045] This embodiment provides a flexible optical cable skin with strong bending resistance, comprising the following components in parts by weight: 100 parts of modified polyvinyl chloride, 17 parts of PBT resin, 20 parts of modified filler, 62 parts of plasticizer, 0.6 parts of lubricant, 1.5 parts of anti-hydrolysis agent and 2 parts of molding agent; the plasticizer is trioctyl trimellitate. The molding agent is an acrylic ester copolymer. The anti-hydrolysis agent is polycarbodiimide. The lubricant is natural paraffin.

[0046] The preparation method of modified polyvinyl chloride comprises the following steps:

[0047] (1) A mixture of nitrile rubber, vinyl silicone oil, dicumyl peroxide and toluene in a weight ratio of 100:22:1.7:880 was mixed and stirred at 28°C for 1.6 hours to obtain a mixed solution, which was reacted at 105°C for 4.5 hours under nitrogen protection, cooled, ethanol precipitated, and dried to obtain a modified nitrile rubber; the vinyl silicone oil had a molecular weight of 9400 and a vinyl content of 0.4-0.6wt%. The vinyl silicone oil was purchased from Anhui Mingyi Silicon Industry Co., Ltd., model MY273.

[0048] (2) Mixing polyvinyl chloride and modified nitrile rubber in a weight ratio of 100:13 to obtain a mixed raw material; putting the mixed raw material into a twin-screw extruder for reaction for 17 minutes, and extruding, the temperature of each zone of the twin-screw extruder is as follows: 180°C for zone 1, 210°C for zone 2, 210°C for zone 3, 220°C for zone 4, 200°C for zone 5, 200°C for zone 6, 210°C for zone 7, 210°C for zone 8, 20°C for zone 9, and 200°C for die head; pelletizing and drying to obtain modified polyvinyl chloride.

[0049] The polyvinyl chloride resin includes polyvinyl chloride resin I, polyvinyl chloride resin II and polyvinyl chloride resin III in a weight ratio of 1.6:1:0.4; the average degree of polymerization of polyvinyl chloride resin I is 1300±50, the K value is 71-72, Formosa Plastics Industry (Ningbo) Co., Ltd., model S-70R; the average degree of polymerization of polyvinyl chloride resin II is 2500±200, the K value is 84-85, Formosa Plastics Industry (Ningbo) Co., Ltd., model S-85; the average degree of polymerization of polyvinyl chloride resin III is 1800±50, the K value is 77-78, Formosa Plastics Industry (Ningbo) Co., Ltd., model S-80.

[0050] PBT resin includes PBT resin I, PBT resin II and PBT resin III with a weight ratio of 0.4:1.5:1. PBT resin I has a melt flow rate of 80g / 10min at 250℃ / 2.16kg, a tensile modulus of 2700MPa, and a flexural modulus of 2500MPa at a span of 50.0mm. Model: HX215HP SabicValoxPBT; PBT resin II has a melt flow rate of 2 at 250℃ / 2.16kg. 6g / 10min, tensile modulus is 9300MPa, and flexural modulus with a span of 50.0mm is 7580MPa. Model: HX420HP SabicValoxPBT; PBT resin III has a melt flow rate of 12g / 10min at 250℃ / 2.16kg, a tensile modulus of 8840MPa, and a flexural modulus with a span of 50.0mm is 7400MPa. Model: K4560 SabicValoxPBT.

[0051] The preparation method of the modified filler comprises the following steps:

[0052] (1) mixing single-walled carbon nanotubes, nano-alumina and nano-silicon dioxide in a weight ratio of 1:1.3:0.6 to obtain a mixed filler;

[0053] (2) Mixing a mixed filler, anhydrous ethanol and KH550 in a weight ratio of 1:11:0.3, stirring and reacting at 58° C. for 5 h, filtering, washing and drying to obtain a pre-modified filler;

[0054] (3) Pre-modified filler, anhydrous ethanol, glycidyl methacrylate and azobisisobutyronitrile were mixed in a weight ratio of 1:9:0.17:0.03, heated at 62° C. with stirring for 7 h, filtered, washed and dried to obtain a modified filler.

[0055] The single-walled carbon nanotube has a diameter of 1-2 nm, a length of 5-30 μm, and a specific surface area of ​​120 m 2 / g; the particle size of nano-alumina is 15-20nm, and the specific surface area is 150-200m 2 / g; the particle size of nano-silicon dioxide is 10-15nm, and the specific surface area is 250m 2 / g.

[0056] The method for preparing a flexible optical cable skin with strong bending resistance comprises the following steps: adding modified polyvinyl chloride, modified filler, plasticizer, lubricant and anti-hydrolysis agent to a high-speed mixer in sequence, controlling the temperature at 157° C. and mixing for 20 minutes; cooling to 102° C. and adding a molding agent, mixing for 5 minutes, heating to 147° C. and adding PBT resin, mixing for 15 minutes,

[0057] The material can be discharged and added into a twin-screw extruder granulator to extrude and granulate at 135° C. to obtain optical cable material, and the optical cable material is prepared into an optical cable skin, that is, a flexible optical cable skin with strong bending resistance.

[0058] Example 2

[0059] This embodiment provides a flexible optical cable skin with strong bending resistance, comprising the following components in parts by weight: 100 parts of modified polyvinyl chloride, 20 parts of PBT resin, 23 parts of modified filler, 60 parts of plasticizer, 0.4 parts of lubricant, 1 part of anti-hydrolysis agent and 3 parts of molding agent; the plasticizer is trioctyl trimellitate. The molding agent is an acrylic ester copolymer. The anti-hydrolysis agent is polycarbodiimide. The lubricant is liquid paraffin.

[0060] The preparation method of modified polyvinyl chloride comprises the following steps:

[0061] (1) A mixture of nitrile rubber, vinyl silicone oil, dicumyl peroxide and toluene in a weight ratio of 100:20:1:900 was mixed and stirred at 25°C for 2 hours to obtain a mixed solution, which was reacted at 100°C for 5 hours under nitrogen protection, cooled, ethanol precipitated, and dried to obtain a modified nitrile rubber; the vinyl silicone oil had a molecular weight of 9400 and a vinyl content of 0.4-0.6wt%. The vinyl silicone oil was purchased from Anhui Mingyi Silicon Industry Co., Ltd., model MY273.

[0062] (2) Mixing polyvinyl chloride and modified nitrile rubber in a weight ratio of 100:11 to obtain a mixed raw material; putting the mixed raw material into a twin-screw extruder for reaction for 20 minutes, and extruding, the temperature of each zone of the twin-screw extruder is as follows: 180°C for zone 1, 200°C for zone 2, 210°C for zone 3, 210°C for zone 4, 200°C for zone 5, 200°C for zone 6, 200°C for zone 7, 210°C for zone 8, 210°C for zone 9, and 200°C for die head; pelletizing and drying to obtain modified polyvinyl chloride.

[0063] The polyvinyl chloride resin includes polyvinyl chloride resin I, polyvinyl chloride resin II and polyvinyl chloride resin III in a weight ratio of 1.4:1:0.5; the average degree of polymerization of polyvinyl chloride resin I is 1300±50, the K value is 71-72, Formosa Plastics Industry (Ningbo) Co., Ltd., model S-70R; the average degree of polymerization of polyvinyl chloride resin II is 2500±200, the K value is 84-85, Formosa Plastics Industry (Ningbo) Co., Ltd., model S-85; the average degree of polymerization of polyvinyl chloride resin III is 1800±50, the K value is 77-78, Formosa Plastics Industry (Ningbo) Co., Ltd., model S-80.

[0064] PBT resin includes PBT resin I, PBT resin II and PBT resin III with a weight ratio of 0.2:1.4:1. PBT resin I has a melt flow rate of 80g / 10min at 250℃ / 2.16kg, a tensile modulus of 2700MPa, and a flexural modulus of 2500MPa at a span of 50.0mm. Model: HX215HP SabicValoxPBT; PBT resin II has a melt flow rate of 2 at 250℃ / 2.16kg. 6g / 10min, tensile modulus is 9300MPa, and flexural modulus with a span of 50.0mm is 7580MPa. Model: HX420HP SabicValoxPBT; PBT resin III has a melt flow rate of 12g / 10min at 250℃ / 2.16kg, a tensile modulus of 8840MPa, and a flexural modulus with a span of 50.0mm is 7400MPa. Model: K4560 SabicValoxPBT.

[0065] The preparation method of the modified filler comprises the following steps:

[0066] (1) mixing single-walled carbon nanotubes, nano-alumina and nano-silicon dioxide in a weight ratio of 1:1.2:0.5 to obtain a mixed filler;

[0067] (2) Mixing a mixed filler, anhydrous ethanol and KH550 in a weight ratio of 1:10:0.4, stirring and reacting at 55° C. for 6 h, filtering, washing and drying to obtain a pre-modified filler;

[0068] (3) Pre-modified filler, anhydrous ethanol, glycidyl methacrylate and azobisisobutyronitrile were mixed in a weight ratio of 1:8:0.15:0.04, heated at 65° C. with stirring for 6 h, filtered, washed and dried to obtain a modified filler.

[0069] The single-walled carbon nanotube has a diameter of 1-2 nm, a length of 5-30 μm, and a specific surface area of ​​120 m 2 / g; the particle size of nano-alumina is 15-20nm, and the specific surface area is 150-200m 2 / g; the particle size of nano-silicon dioxide is 10-15nm, and the specific surface area is 250m 2 / g.

[0070] The method for preparing a flexible optical cable skin with strong bending resistance comprises the following steps: adding modified polyvinyl chloride, modified filler, plasticizer, lubricant and anti-hydrolysis agent to a high-speed mixer in sequence, controlling the temperature at 160° C. and mixing for 15 minutes; cooling to 105° C. and adding a molding agent, mixing for 5 minutes, heating to 150° C. and adding PBT resin, mixing for 15 minutes,

[0071] The material can be discharged and added into a twin-screw extruder granulator to extrude and granulate at 135° C. to obtain optical cable material, and the optical cable material is prepared into an optical cable skin, that is, a flexible optical cable skin with strong bending resistance.

[0072] Comparative Example 1

[0073] The difference between this comparative example and Example 1 is that the modified polyvinyl chloride is replaced by polyvinyl chloride. The polyvinyl chloride resin includes polyvinyl chloride resin I, polyvinyl chloride resin II and polyvinyl chloride resin III in a weight ratio of 1.6:1:0.4; the average polymerization degree of polyvinyl chloride resin I is 1300±50, the K value is 71-72, Formosa Plastics Industry (Ningbo) Co., Ltd., model S-70R; the average polymerization degree of polyvinyl chloride resin II is 2500±200, the K value is 84-85, Formosa Plastics Industry (Ningbo) Co., Ltd., model S-85; the average polymerization degree of polyvinyl chloride resin III is 1800±50, the K value is 77-78, Formosa Plastics Industry (Ningbo) Co., Ltd., model S-80.

[0074] Comparative Example 2

[0075] The difference between this comparative example and Example 1 is that the polyvinyl chloride resin includes polyvinyl chloride resin I, polyvinyl chloride resin II and polyvinyl chloride resin III in a weight ratio of 1:1:1; the average degree of polymerization of polyvinyl chloride resin I is 1300±50, the K value is 71-72, Formosa Plastics Industry (Ningbo) Co., Ltd., model S-70R; the average degree of polymerization of polyvinyl chloride resin II is 2500±200, the K value is 84-85, Formosa Plastics Industry (Ningbo) Co., Ltd., model S-85; the average degree of polymerization of polyvinyl chloride resin III is 1800±50, the K value is 77-78, Formosa Plastics Industry (Ningbo) Co., Ltd., model S-80.

[0076] Comparative Example 3

[0077] The difference between this comparative example and Example 1 is that the vinyl silicone oil has a molecular weight of 6000 and a vinyl content of 0.8-1.2 wt %, and is purchased from Anhui Mingyi Silicon Industry Co., Ltd.

[0078] Comparative Example 4

[0079] The difference between this comparative example and Example 1 is that the PBT resin includes PBT resin I, PBT resin II and PBT resin III in a weight ratio of 1:1:1, PBT resin I has a melt flow rate of 80g / 10min at 250°C / 2.16kg, a tensile modulus of 2700MPa, and a flexural modulus of 2500MPa at a span of 50.0mm, model: HX215HP SabicValoxPBT; PBT resin II ... The moving rate is 26g / 10min, the tensile modulus is 9300MPa, and the bending modulus with a span of 50.0mm is 7580MPa. Model: HX420HP SabicValoxPBT; the melt flow rate of PBT resin III at 250℃ / 2.16kg is 12g / 10min, the tensile modulus is 8840MPa, and the bending modulus with a span of 50.0mm is 7400MPa. Model: K4560 SabicValoxPBT.

[0080] Comparative Example 5

[0081] The difference between this comparative example and Example 1 is that the PBT resin is PBT resin II; PBT resin II has a melt flow rate of 26 g / 10 min at 250°C / 2.16 kg, a tensile modulus of 9300 MPa, and a flexural modulus of 7580 MPa at a span of 50.0 mm, and the model number is HX420HP SabicValoxPBT.

[0082] Comparative Example 6

[0083] The difference between this comparative example and Example 1 is that the diameter of the single-walled carbon nanotube is 4-6 nm, the length is 20-30 μm, and the specific surface area is 80 m 2 / g; the particle size of nano-alumina is 20-30nm, and the specific surface area is 50-100m 2 / g; the particle size of nano-silicon dioxide is 10-15nm, and the specific surface area is 250m 2 / g.

[0084] Comparative Example 7

[0085] The difference between this comparative example and Example 1 is that single-walled carbon nanotubes, nano-alumina and nano-silicon dioxide are mixed in a weight ratio of 1:1:1 to obtain a mixed filler.

[0086] Comparative Example 8

[0087] The difference between this comparative example and Example 1 is that the preparation method of the modified filler comprises the following steps:

[0088] (1) mixing single-walled carbon nanotubes, nano-alumina and nano-silicon dioxide in a weight ratio of 1:1.3:0.6 to obtain a mixed filler;

[0089] (2) Mix the mixed filler, anhydrous ethanol and KH550 in a weight ratio of 1:11:0.3, stir and react at 58° C. for 5 h, filter, wash and dry to obtain a modified filler.

[0090] Performance Testing

[0091] The optical cable materials prepared in Examples 1-2 and Comparative Examples 1-8 were subjected to performance tests.

[0092] 1. Use a universal tensile tester to measure the tensile properties according to UL1581 Table 50181, Section 470, Plastic Tensile Properties Test Method;

[0093] 2. Use a flexure tester and refer to UL1581 Table 50181, Wire Bending Test Method, to conduct a 45° flexure test and count the number of times no cracking occurs;

[0094] 3. Use a low temperature test chamber and refer to Section 580-583 of UL1581, low temperature bending test method, to measure the -20℃ low temperature bending performance;

[0095] 4. Oil resistance: Soak in Mobil Vectra 3# guide rail oil at 25°C for 300 hours. If the oil swelling change rate is less than 5%, it is considered passed, otherwise it is considered failed. Oil swelling change rate = (Df-Di) / Di; Di is the initial volume of the sample before oil immersion; Df is the final volume of the sample after oil immersion.

[0096] Table 1 Performance test results

[0097]

[0098] From the above performance test results, it can be seen that the optical cable materials prepared in Examples 1-2 have excellent performance, and the optical cable skin prepared therefrom has better performance, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic compounding between the components.

[0099] However, the comparative examples are obviously inferior to the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, the modified polyvinyl chloride is replaced by polyvinyl chloride, and the tensile properties of the optical cable material decrease; in comparative example 2, the polyvinyl chloride resin ratio is different, the tensile properties of the optical cable material decrease, and the low-temperature bending performance decreases; in comparative example 3, the vinyl silicone oil is different, and the tensile properties of the optical cable material decrease; in comparative examples 4 and 5, the PBT resin composition is different, the durability of the optical cable under repeated bending conditions decreases, and the low-temperature bending performance decreases; in comparative example 6, the filler parameters are different, the oil resistance of the optical cable material decreases, and the low-temperature bending performance decreases; in comparative example 7, the filler ratio is different; in comparative example 8, the preparation method of the filler is different, and the oil resistance of the optical cable material decreases. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0100] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A flexible optical cable skin with strong bending resistance, characterized in that: The invention comprises the following components in parts by weight: 100 parts of modified polyvinyl chloride, 15-20 parts of PBT resin, 18-23 parts of modified filler, 60-65 parts of plasticizer, 0.4-0.9 parts of lubricant, 1-2 parts of anti-hydrolysis agent and 1-3 parts of molding agent; The preparation method of modified polyvinyl chloride comprises the following steps: (1) mixing nitrile rubber, vinyl silicone oil, dicumyl peroxide and toluene in a weight ratio of 100:(20-25):(1-2):(870-900), stirring at 25-30° C. for 1-2 hours to obtain a mixed solution, reacting the mixed solution at 100-110° C. for 4-5 hours under nitrogen protection, cooling, ethanol precipitation, and drying to obtain a modified nitrile rubber; (2) Mixing polyvinyl chloride and modified nitrile rubber in a weight ratio of 100:(10-15) to obtain a mixed raw material; putting the mixed raw material into a twin-screw extruder to react for 15-20 minutes, extruding, pelletizing, and drying to obtain modified polyvinyl chloride.

2. The flexible optical cable skin with strong bending resistance according to claim 1 is characterized in that: The molecular weight of the vinyl silicone oil is 9400, and the vinyl content is 0.4-0.6 wt%.

3. The flexible optical cable skin with strong bending resistance according to claim 1 is characterized in that: The polyvinyl chloride resin includes polyvinyl chloride resin I, polyvinyl chloride resin II and polyvinyl chloride resin III in a weight ratio of (1.4-1.7):1:(0.3-0.5); the average degree of polymerization of polyvinyl chloride resin I is 1300±50, and the K value is 71-72; the average degree of polymerization of polyvinyl chloride resin II is 2500±200, and the K value is 84-85; the average degree of polymerization of polyvinyl chloride resin III is 1800±50, and the K value is 77-78.

4. The flexible optical cable skin with strong bending resistance according to claim 1, characterized in that: The PBT resin includes PBT resin I, PBT resin II and PBT resin III in a weight ratio of (0.2-0.5):(1.4-1.6):

1. The melt flow rate of PBT resin I at 250°C / 2.16kg is 80g / 10min, the tensile modulus is 2700MPa, and the bending modulus at a span of 50.0mm is 2500MPa; the melt flow rate of PBT resin II at 250°C / 2.16kg is 26g / 10min, the tensile modulus is 9300MPa, and the bending modulus at a span of 50.0mm is 7580MPa; the melt flow rate of PBT resin III at 250°C / 2.16kg is 12g / 10min, the tensile modulus is 8840MPa, and the bending modulus at a span of 50.0mm is 7400MPa.

5. The flexible optical cable skin with strong bending resistance according to claim 1, characterized in that: The preparation method of the modified filler comprises the following steps: (1) mixing single-walled carbon nanotubes, nano-alumina and nano-silicon dioxide in a weight ratio of 1: (1.2-1.4): (0.5-0.7) to obtain a mixed filler; (2) Mixing a mixed filler, anhydrous ethanol and KH550 in a weight ratio of 1: (10-12): (0.2-0.4), stirring and reacting at 55-60° C. for 4-6 hours, filtering, washing and drying to obtain a pre-modified filler; (3) Pre-modified filler, anhydrous ethanol, glycidyl methacrylate and azobisisobutyronitrile in weight parts of 1: (8-10): (0.15-0.18): (0.02-0.04) are mixed, heated at 60-65° C. with stirring for 6-8 hours, filtered, washed and dried to obtain a modified filler.

6. The flexible optical cable skin with strong bending resistance according to claim 5, characterized in that: The single-walled carbon nanotube has a diameter of 1-2 nm, a length of 5-30 μm, and a specific surface area of ​​120 m 2 / g; the particle size of nano-alumina is 15-20nm, and the specific surface area is 150-200m 2 / g; the particle size of nano-silicon dioxide is 10-15nm, and the specific surface area is 250m 2 / g.

7. The flexible optical cable skin with strong bending resistance according to claim 1, characterized in that: The plasticizer is adipic acid polyester or trioctyl trimellitate.

8. The flexible optical cable skin with strong bending resistance according to claim 1, characterized in that: The anti-hydrolysis agent is polycarbodiimide.

9. The flexible optical cable skin with strong bending resistance according to claim 1, characterized in that: The lubricant is at least one of natural paraffin, liquid paraffin, microcrystalline paraffin and polyethylene wax.

10. A method for preparing a flexible optical cable skin with strong bending resistance according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: adding modified polyvinyl chloride, modified filler, plasticizer, lubricant and anti-hydrolysis agent into a high-speed mixer in sequence, controlling the temperature at 155-160 DEG C, and mixing for 15-20 minutes; cooling to 100-105 DEG C, adding a molding agent, mixing for 5-10 minutes, heating to 145-150 DEG C, adding PBT resin, mixing for 10-15 minutes, discharging the material, adding the material into a twin-screw extruder granulator, extruding and granulating at 135-140 DEG C to obtain optical cable material, and preparing the optical cable material into an optical cable skin, namely, a flexible optical cable skin with strong anti-bending performance.